A rare case of primary infertility with bilateral agenesis of medial part of fimbrial end with hypoplasia of fimbria and absence of fimbria ovarica with septate uterus with bilateral normal ovaries - Tandulwadkar, Sunita; Mishra, Sneha; Gupta, Shruti; Singh, Akhileshwar; Singhania, Samta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Patients with infertility frequently present with associated congenital genital anomalies affecting around 5-6% of patients. Most of these patients have anomalies associated with uterus, cervix and vagina which have been extensively studied through time. The exact association of abnormalities of fallopian tube to infertility is still unknown due to the limited data available. The true incidence of congenital fallopian tube anomalies is unknown because abnormalities may be subtle and are often overlooked or thought to be due to acquired or iatrogenic causes. While reviewing the literature, we observed that partial or complete agenesis of the fallopian tube is rarely reported. They are usually incidental diagnosis on laparoscopy done for some other purposes. Due to rarity of such cases, their effect on fertility and its management is still a challenge. Here, we present a case report of septate uterus with bilateral fimbrial agenesis and normal ovaries in a patient of primary infertility.